Investigations into photoreceptor energy metabolism during experimental retinal detachment - Chidlow, Glyn; Chan, Weng Onn; Wood, John P. M.; Casson, Robert J. (Frontiers in Cellular Neuroscience, 2022)
Retinal detachment is a sight-threatening disorder, which occurs when the photoreceptors are separated from their vascular supply. The aim of the present study was to shed light on photoreceptor energy metabolism during experimental detachment in rats. Retinal detachment was induced in the eyes of rats via subretinal injection of sodium hyaluronate. Initially, we investigated whether detachment caused hypoxia within photoreceptors, as evaluated by the exogenous and endogenous biomarkers pimonidazole and HIF-1, as well as by qPCR analysis of HIF target genes. The results showed no unequivocal staining for pimonidazole or HIF-1 within any detached retina, nor upregulation of HIF target genes, suggesting that any reduction in pO2 is of insufficient magnitude to produce hypoxia-induced covalent protein adducts or HIF-1 stabilization. Subsequently, we analysed expression of cellular bioenergetic enzymes in photoreceptors during detachment. We documented loss of mitochondrial, and downregulation of glycolytic enzymes during detachment, indicating that photoreceptors have reduced energetic requirements and/or capacity. Given that detachment did not cause widespread hypoxia, but did result in downregulated expression of bioenergetic enzymes, we hypothesized that substrate insufficiency may be critical in terms of pathogenesis, and that boosting metabolic inputs may preserve photoreceptor bioenergetic production and, protect against their degeneration. Thus, we tested whether supplementation with the bioavailable energy substrate pyruvate mitigated rod and cone injury and degeneration. Despite protecting photoreceptors in culture from nutrient deprivation, pyruvate failed to protect against apoptotic death of rods, loss of cone opsins, and loss of inner segment mitochondria, in situ, when evaluated at 3 days after detachment. The regimen was also ineffective against cumulative photoreceptor deconstruction and degeneration when evaluated after 4 weeks. Retinal metabolism, particularly the bioenergetic profiles and pathological responses of the various cellular subtypes still presents a considerable knowledge gap that has important clinical consequences. While our data do not support the use of pyruvate supplementation as a means of protecting detached photoreceptors, they do provide a foundation and motivation for future research in this area.